1997
DOI: 10.1093/geronb/52b.5.p247
|View full text |Cite
|
Sign up to set email alerts
|

The Modified Fuld Verbal Fluency Test: A Validation Study in Hong Kong

Abstract: Recent studies in the West have found that verbal fluency tests are useful in the detection of dementia. In this study, the Fuld Verbal Fluency Test (FVFT) was modified and tested for its usefulness as a screening instrument for differentiating demented from normal elderly Chinese in Hong Kong. Fifty-three normal and 56 demented subjects were administered the FVFT, the Cantonese version of the Mini-Mental State Examination (CMMSE), and the Chinese version of the Hamilton Depression Rating Scale. In addition to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 15 publications
0
36
1
Order By: Relevance
“…Combined VFT scores (NC group, 36.2 B 7.3; AD subjects, 20.7 B 7.8) differed from a related previous study (non-demented controls, 29.7 B 8.2; demented subjects, 14.0 B 7.9) [28]. Such differences were related to differences in the test administration procedure.…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…Combined VFT scores (NC group, 36.2 B 7.3; AD subjects, 20.7 B 7.8) differed from a related previous study (non-demented controls, 29.7 B 8.2; demented subjects, 14.0 B 7.9) [28]. Such differences were related to differences in the test administration procedure.…”
Section: Discussioncontrasting
confidence: 68%
“…Category VFT was conducted in Cantonese in this study. Three semantic categories ('food', 'fruit' and 'vegetable') were chosen in accordance with the test used by Chiu et al [28]. The procedure was slightly modified for standardization.…”
Section: Assessment Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The cut-off scores were selected based on the generally accepted cut-off score or results from local validation study [25][26][27]. According to this classification system, subjects were divided into groups having 0 to 3 tests with scores above the cut-off value.…”
Section: Resultsmentioning
confidence: 99%
“…However, the characteristics of the CVFT in Chinese subjects with AD have been examined [9,10] , and it has been found that performance in the CVFT is significantly associated with age and educational level in cognitively intact elderly people. In subjects with AD, CVFT performance is associated with cognitive functioning and is a sensitive test for the screening of dementia.…”
mentioning
confidence: 99%